Exercising societal marketing concept: employees of PKNS and public perception. A case study of Perbadanan Kemajuan Negeri Selangor (PKNS) Petaling Jaya 2005 / Haliza Mazlin Abdul Halim - Abdul Halim, Haliza Mazlin (Faculty of Business and Management, 2005)
Societal marketing concept is the marketing concept that preferable by organizations nowadays. It believes that it could lead to better financial performance. The management of marketing concept is also a branch of marketing and management. Reflecting and exercising should be orchestrated together. PKNS practice the societal marketing concept reflect their philosophy through long term and short-term activities. The research gathering data was segregated into three set for each of these populations. The collectives' data indicates the societal marketing concept that exercises by PKNS and percept by public as so. The analyze of the data will segregate the reflective of the societal marketing concept, employee’s exercises working conducts in work, ethics, work culture and work services activities that reflect the exercises of PKNS societal marketing concept and public perception of PKNS whether PKNS did exercise the societal marketing concept. In long term, PKNS established such as mission statement and philosophy. The study on the other hands, mostly cover the short-term activities of PKNS societal marketing concept activities. The mutual concept of societal marketing concept is interrelated. Therefore, the conclusion of effectiveness of exercising societal concept signifies both short and long-term activities success, Beside that, the two mutual concepts also locked together the management, employees and public. The connections are the management decides the societal concept and established the activities for employees. Employees on the other hand, demonstrated the designed activities in their working conducts in areas of work ethics, work culture and work service as anticipated by management mould by the PKNS societal marketing concept. Public perception of PKNS signifies PKNS as a societal marketing concept organization. The imperative of the study has concluded that, the exercises of the societal marketing concept by PKNS employees and public percepts as well. Nonetheless, PKNS can understand that critical aspects to be amend in their employees and social activities that they held, for better contribution to society and public. Lastly, the societal marketing management is indeed important but though organization reflect and exercise the correct societal concept, it cannot contribute to greater sales if the product and service offer is comparatively poor then the organization reflection and exercises of the societal concept.